The blue diatom Haslea ostrearia from the Indian Ocean coast of South Africa, with comparative analysis of Haslea organellar genomes - Dąbek, Przemysław; Gastineau, Romain; Bornman, Thomas G.; Lemieux, Claude; Turmel, Monique; Hallegraeff, Gustaaf; Mouget, Jean-Luc; Witkowski, Andrzej (Frontiers in Marine Science, 2022)
Haslea ostrearia represents the model species of blue diatoms, a cluster of benthic marine species all belonging to the genus Haslea, noticeable for producing a blue pigment called marennine famous for its greening activity on the gills of bivalves but also for its potential in biotechnology. The exact distribution of H. ostrearia is unknown. It has been long considered a cosmopolitan diatom, but recent studies provided evidence for cryptic diversity and the existence of several other blue species, some of them inhabiting places where diatoms described as H. ostrearia had previously been observed. Recently, a marine diatom with blue tips was isolated into clonal culture from a plankton net sample from Kei Mouth on the Indian Ocean coast of South Africa. It was identified as H. ostrearia through a combination of LM/SEM microscopy and molecular analysis. This constitutes the first established record of this species from South Africa and the Indian Ocean and the second record for the southern hemisphere. Molecular barcoding clearly discriminated the South African strain from an Australian strain and cox1 based molecular phylogeny associated it instead with strains from the French Atlantic Coast, raising questions about the dispersal of this species. The complete mitochondrial and plastid genomes were compared to those of Haslea nusantara and Haslea silbo. Multigene phylogenies performed with all protein-coding genes of the plastome and the mitogenome associated H. ostrearia with H. silbo. In addition, complete sequences of circular plasmids were obtained and one of them showed an important conservation with a plasmid found in H. silbo.